Strategy in turbulent times: how to design a strategy that is robust and future-proof - Verweire, Kurt, ....- (Tielt : LannooCampus, 2024)
Companies face increasingly turbulent times. Economic and political uncertainty, sustainability developments, and competitors with new business models are just some issues that stretch companies' resilience and adaptability. Strategy in Turbulent Times presents a way of analyzing and fighting turbulent environments. Using four animal metaphors, the Camel, Salmon, Chameleon and Octopus, it shows you how to develop new strategies and how to implement them. It is up to you to discover which animal represents the appropriate turbulence strategy for your organization
Keywords: Etisch ondernemen